2006
DOI: 10.1038/sj.onc.1209951
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunctional AMPK activity, signalling through mTOR and survival in response to energetic stress in LKB1-deficient lung cancer

Abstract: LKB1, mutated in Peutz-Jeghers and in sporadic lung tumours, phosphorylates a group of protein kinases named AMP-activated protein kinase (AMPK)-related kinases. Among them is included the AMPK, a sensor of cellular energy status. To investigate the relevance of LKB1 in lung carcinogenesis, we study several lung cancer cells with and without LKB1-inactivating mutations. We report that LKB1-mutant cells are deficient for AMPK activity and refractory to mTOR inhibition upon glucose depletion but not growth-facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
101
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(110 citation statements)
references
References 38 publications
9
101
0
Order By: Relevance
“…Germline mutations of TSC1 or TSC2 genes cause the tuberous sclerosis syndrome, which shares similarities with PJS, including the presence of hamartomas (Consortium TECS, 1993). We recently confirmed that wild-type LKB1 is also required for modulating AMPK activity and therefore that of AMPKdownstream targets, including mTOR, in energetically depleted lung cancer cells (Carretero et al, 2007). The identification of AMPK as a key substrate of LKB1 kinase activity provides definitive evidence that the abrogation of energetic checkpoints, probably with the purpose of maintaining energetically costly processes such as DNA replication and cell division, is an obligatory event for cancer development.…”
Section: Lkb1 As An Energetic Checkpoint Controllermentioning
confidence: 64%
“…Germline mutations of TSC1 or TSC2 genes cause the tuberous sclerosis syndrome, which shares similarities with PJS, including the presence of hamartomas (Consortium TECS, 1993). We recently confirmed that wild-type LKB1 is also required for modulating AMPK activity and therefore that of AMPKdownstream targets, including mTOR, in energetically depleted lung cancer cells (Carretero et al, 2007). The identification of AMPK as a key substrate of LKB1 kinase activity provides definitive evidence that the abrogation of energetic checkpoints, probably with the purpose of maintaining energetically costly processes such as DNA replication and cell division, is an obligatory event for cancer development.…”
Section: Lkb1 As An Energetic Checkpoint Controllermentioning
confidence: 64%
“…The mTorc1 hyperactivation has indeed been observed in Lkb1-null mouse embryonic fibroblasts as well as in other murine and human LKB1-deficient cells (Corradetti et al, 2004;Shaw et al, 2004Shaw et al, , 2005Carretero et al, 2007;Contreras et al, 2008;Ikeda et al, 2009). In addition, mTorc1 hyperactivation has been observed in intestinal polyps of Lkb1 þ /À mice and PJS patients, indicating that mTORC1 is hyperactivated in PJS-associated hamartomas (Shaw et al, 2004;Shackelford and Shaw, 2009).…”
Section: Hyperactive Mtorc1 In Lkb1/ampk/tsc-associated Lesionsmentioning
confidence: 81%
“…Although LKB1 restoration can block proliferation or metastasis of some LKB1 mutant cancer cell lines, the mechanism may be non-physiological and/or involve targets that are not relevant to the role of LKB1 in the natural history of the tumor. The role of LKB1 in cancers is particularly difficult to conceptualize as LKB1 deficiency renders both primary cells and cancer cell lines sensitive to cell death in response to energy stress (Shaw et al, 2004b;Carretero et al, 2007;Memmott et al, 2008). Therefore it is likely that specific cooperating molecular alterations are required for LKB1-deficient cells to withstand energy stress during tumor progression.…”
Section: Discussionmentioning
confidence: 99%